Responses of midgut amylases of Helicoverpa armigera to feeding on various host plants - Kotkar, Hemlata M.; Sarate, Priya J.; Tamhane, Vaijayanti A.; Gupta, Vidya S.; Giri, Ashok P. (Journal of Insect Physiology, 2009)
Midgut digestive amylases and proteinases of Helicoverpa armigera, a polyphagous and devastating insect pest of economic importance have been studied. We also identified the potential of a sorghum amylase inhibitor against H. armigera midgut amylase. Amylase activities were detected in all the larval instars, pupae, moths and eggs; early instars had lower amylase levels which steadily increased up to the sixth larval instar. Qualitative and quantitative differences in midgut amylases of H. amigera upon feeding on natural and artificial diets were evident. Natural diets were categorized as one or more members of legumes, vegetables, flowers and cereals belonging to different plant families. Amylase activity and isoform patterns varied depending on host plant and/or artificial diet. Artificial diet-fed H. armigera larvae had comparatively high amylase activity and several unique amylase isoforms. Correlation of amylase and proteinase activities of H. armigera with the protein and carbohydrate content of various diets suggested that H. armigera regulates the levels of these digestive enzymes in response to macromolecular composition of the diet. These adjustments in the digestive enzymes of H. armigera may be to obtain better nourishment from the diet and avoid toxicity due to nutritional imbalance. H. armigera, a generalist feeder experiences a great degree of nutritional heterogeneity in its diet. An investigation of the differences in enzyme levels in response to macronutrient balance and imbalance highlight their importance in insect nutrition. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Amylase inhibitors; Diet; Helicoverpa armigera larvae; Midgut amylase; Proteinases

Resistome analysis of mycobacterium tuberculosis: identification of aminoglycoside 2’-nacetyltransferase (AAC) as co-target for drug desigining - Joshi R. S.; Jamdhade M. D.; Sonawane M. S.; Giri, Ashok P. (Bioinformation, 2013)
The emergence of multidrug resistant tuberculosis (MDRTB) highlights the urgent need to understand the mechanisms of resistance to the drugs and to develop a new arena of therapeutics to treat the disease. Ethambutol, isonazid, pyrazinamide, rifampicin are first line of drugs against TB, whereas aminoglycoside, polypeptides, fluoroquinolone, ethionamide are important second line of bactericidal drugs used to treat MDRTB, and resistance to one or both of these drugs are defining characteristic of extensively drug resistant TB. We retrieved 1,221 resistant genes from Antibiotic Resistance Gene Database (ARDB), which are responsible for resistance against first and second line antibiotics used in treatment of Mycobacterium tuberculosis infection. From network analysis of these resistance genes, 53 genes were found to be common. Phylogenetic analysis shows that more than 60% of these genes code for acetyltransferase. Acetyltransferases detoxify antibiotics by acetylation, this mechanism plays central role in antibiotic resistance. Seven acetyltransferase (AT-1 to AT-7) were selected from phylogenetic analysis. Structural alignment shows that these acetyltransferases share common ancestral core, which can be used as a template for structure based drug designing. From STRING analysis it is found that acetyltransferase interact with 10 different proteins and it shows that, all these interaction were specific to M. tuberculosis. These results have important implications in designing new therapeutic strategies with acetyltransferase as lead co-target to combat against MDR as well as Extreme drug resistant (XDR) tuberculosis.

Remarkable efficiency of a pin-II proteinase inhibitor sans two conserved disulfide bonds is due to enhanced flexibility and hydrogen bond density in the reactive site loop - Joshi, Rakesh S.; Mishra, Manasi; Tamhane, Vaijayanti A.; Ghosh, Anirban; Sonavane, Uddhavesh; Suresh, C. G.; Joshi, Rajendra; Gupta, Vidya S.; Giri, Ashok P. (Journal of Biomolecular Structure & Dynamics, 2014)
Capsicum annuum (L.) expresses diverse potato type II family proteinase inhibitors comprising of inhibitory repeat domain (IRD) as basic functional unit. Most IRDs contain eight conserved cysteines forming four disulfide bonds, which are indispensible for their stability and activity. We investigated the functional significance of evolutionary variations in IRDs and their role in mediating interaction between the inhibitor and cognate proteinase. Among the 18 IRDs encoded by C. annuum, IRD-7, -9, and -12 were selected for further characterization on the basis of variation in their reactive site loop, number of conserved cysteine residues, and higher theoretical G(bind) for interaction with Helicoverpa armigera trypsin. Moreover, inhibition kinetics showed that IRD-9, despite loss of some of the disulfide bonds, was a more potent proteinase inhibitor among the three selected IRDs. Molecular dynamic simulations revealed that serine residues in the place of cysteines at seventh and eighth positions of IRD-9 resulted in an increase in the density of intramolecular hydrogen bonds and reactive site loop flexibility. Results of the serine residues chemical modification also supported this observation and provided a possible explanation for the remarkable inhibitory potential of IRD-9. Furthermore, this natural variant among IRDs showed special attributes like stability to proteolysis and synergistic inhibitory effect on other IRDs. It is likely that IRDs have coevolved selective specialization of their structure and function as a response towards specific insect proteases they encountered. Understanding the molecular mechanism of pest protease-plant proteinaceous inhibitor interaction will help in developing effective pest control strategies.An animated interactive 3D complement (I3DC) is available in Proteopedia at http://proteopedia.org/w/Journal:JBSD:39
Keywords: Capsicum annuum; Helicoverpa armigera; Proteases; Proteinase inhibitor

Resistance through inhibition: ectopic expression of serine protease inhibitor offers stress tolerance via delayed senescence in yeast cell - Joshi, Rakesh S.; Tanpure, Rahul S.; Singh, Rajan Kumar; Gupta, Vidya S.; Giri, Ashok P. (Biochemical and Biophysical Research Communications, 2014)
Protease inhibitors have been known to confer multiple stress tolerance in transgenic plants. We have assessed growth of yeast (Pichia pastoris GS115) strains expressing inhibitory repeat domains (PpIRD(+)) of previously characterized Capsicum annuum protease inhibitors under high salt, heavy metal and oxidative stress. PpIRD(+) strains exhibited multiple stress tolerance and showed differential molecular responses at transcriptional and translational level on exposure to stress inducing agents like heavy metal, high salt and H2O2. PpIRD(+) strains display significant reduction in metacaspase (Yca1) activity, the key enzyme in apoptosis, indicates the possibility of cross reactivity of IRDs (serine protease inhibitor) with cysteine proteases. PpIRD(+) and Saccharomyces cerevisiae knockout with Yca1 (Delta Yca1) strain showed similar growth characteristics under stress, which indicated the delayed senescence due to cellular metacaspase inhibition. Molecular docking study showed a close proximity of IRDs reactive site and the active site of metacaspase in the complex that signified their strong interactions. Maintenance of GAPDH activity, primary target of metacaspase, in PpIRD(+) strain evidenced the inhibition of metacaspase activity and survival of these cells under stress. This report demonstrates a potential molecular mechanism of protease inhibitor-based multiple stress tolerance in yeast strains. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Metacaspase; Multiple stress tolerance; protease inhibitor; Yeast

RNAi of selected candidate genes interrupts growth and development of Helicoverpa armigera - Chikate, Yojana R.; Dawkar, Vishal V.; Barbole, Ranjit S.; Tilak, Priyadarshini V.; Gupta, Vidya S.; Giri, Ashok P. (Pesticide Biochemistry and Physiology, 2016)
Helicoverpa armigera is one of the major crop pests and is less amenable to current pest control approaches. RNA interference (RNAi) is emerging as a potent arsenal for the insect pest control over current methods. Here, we examined the effect on growth and development in H. armigera by targeting various enzymes/proteins such as proteases like trypsins (HaTry2, 3, 4 and 6), chymotrypsin (HaChy4) and cysteine protease like cathepsin (HaCATHL); glutathione S-transferases (HaGST1a, 6 and 8); esterases (HaAce4, HaJHE); catalase (HaCAT); super-oxide-dismutase (HaCu/ZnSOD); fatty acid binding protein (HaFabp) and chitin deacetylase (HaCda5b) through dsRNA approach. Significant downregulation of cognate mRNA expression and reduced activity of trypsin and GST-like enzyme were evident upon feeding candidate dsRNAs to the larvae. Among these, the highest mortality was observed in HaAce4 dsRNA fed larvae followed by HaJHE; HaCAT; HaCuZnSOD; HaFabp and HaTry3 whereas remaining ones showed relatively lower mortality. Furthermore, the dsRNA fed larvae showed significant reduction in the larval mass and abnormalities at the different stages of H. armigera development compared to their control diets. For example, malformed larvae, pupae and moth at a dose of 60 pg/day were evident in high number of individual insects fed on dsRNA containing diets. Moreover, the growth and development of insects and moths were retarded in dsRNA fed larvae. These findings might provide potential new candidates for designing effective dsRNA as pesticide in crop protection. (C) 2016 Elsevier Inc. All rights reserved.

Rootless survivors in plants - Kondhare, Kirtikumar R.; Lavhale, Santosh G.; Giri, Ashok P. (Plant Science, 2026)
The root system provides anchorage, uptakes of nutrients and water, and forms different associations within soil environments that govern plant fitness, crop performance, and yield. Auxin controls almost all aspects of root development. Both shoot- and root-derived auxins contribute to formation of polar auxin transport, which is crucial for establishing and maintaining normal root architecture. The coordinated activities of auxin influx and efflux carriers establish necessary polar auxin transport. A variety of natural metabolites and synthetic compounds are shown to interfere with auxin metabolism, transporters and signaling pathways having a negative impact on root growth. In this review, we highlight the reports demonstrating the observance of rootless phenotypes in plants and associated molecular mechanisms. Rootless phenotypes can be produced under in vitro culture conditions by modulation of phytohormone combinations (especially auxin and cytokinin), and supplementation of naturally-occurring flavonoids and their glycosides or synthetic auxin transport inhibitors (1-Nnaphthylphthalamic acid and 2,3,5-triiodobenzoic acid) or under in vivo conditions by modulation of several genes directly or indirectly associated with auxin biology. Further, we describe the crosstalk of naturallyoccurring flavonoids (e.g. kaempferol, quercetin), their glycosides, and other metabolites (e.g. azelaic acid, cis-cinnamic acid) with auxin transporters, their mobile nature, and influence on root development. Moreover, we provide evolutionary perspective on the auxin and flavonoid pathways and their possible roles in naturally rootless plants. We also emphasize the importance of rootless or reduced root growth phenotypes in modern agriculture, and the pressing needs to utilize naturally occurring auxin transport inhibitors for industrial and research applications.
Keywords: Auxin; Flavonoid; Flavonoid-glycoside; Polar auxin transport; rootless